Answer:
The number of student's tickets sold was 7
Step-by-step explanation:
Let
x ----> number of adult's tickets sold
y ----> number of student's tickets sold
we know that
[tex]x+y=23[/tex] ----> [tex]x=23-y[/tex] ---> equation A
[tex]13x+9y=271[/tex] ----> equation B
solve the system by substitution
substitute equation A in equation B
[tex]13(23-y)+9y=271[/tex]
solve for y
[tex]299-13y+9y=271[/tex]
[tex]13y-9y=299-271[/tex]
[tex]4y=28[/tex]
[tex]y=7[/tex]
therefore
The number of student's tickets sold was 7
What is the solution for the equation 6x − 8 = 4x? x = ___. (Input whole number only). (5 points)
Answer:
x = 4
Step-by-step explanation:
6x - 8 = 4x
Bringing all the x's to one side and the whole number to the other,
6x - 4x = 8
2x = 8
Therefore, x = 4
Answer:
6x-8=4x
Bring over 4x to the other side of the equation
2x-8=0
2x=8
x=4
please help! 9,000÷900=?
Answer:it is 10%
Step-by-step explanation:
Please, I need help in this ??
Answer:
[tex]\int\frac{x^{4}}{x^{4} -1}dx = x + \frac{1}{4} ln(x-1) - \frac{1}{4} ln(x+1)-\frac{1}{2} arctanx + c[/tex]
Step-by-step explanation:
[tex]\int\frac{x^{4}}{x^{4} -1}dx[/tex]
Adding and Subtracting 1 to the Numerator
[tex]\int\frac{x^{4} - 1 + 1}{x^{4} -1}dx[/tex]
Dividing Numerator seperately by [tex]x^{4} - 1[/tex]
[tex]\int 1 + \frac{1}{x^{4}-1 }\, dx[/tex]
Here integral of 1 is x +c1 (where c1 is constant of integration
[tex]x + c1 + \int\frac{1}{(x-1)(x+1)(x^{2}+1)}\, dx[/tex]----------------------------------(1)
We apply method of partial fractions to perform the integral
[tex]\frac{1}{(x-1)(x+1)(x^{2}+1)}[/tex] = [tex]\frac{A}{x-1} + \frac{B}{x+1} + \frac{C}{x^{2} + 1}[/tex]------------------------------------------(2)
[tex]\frac{1}{(x-1)(x+1)(x^{2}+1)} = \frac{A(x+1)(x^{2} +1) + B(x-1)(x^{2} +1) + C(x-1)(x+1)}{(x-1)(x+1)(x^{2} +1)}[/tex]
1 = [tex]A(x+1)(x^{2} +1) + B(x-1)(x^{2} +1) + C(x-1)(x+1)[/tex]-------------------------(3)
Substitute x= 1 , -1 , i in equation (3)
1 = A(1+1)(1+1)
A = [tex]\frac{1}{4}[/tex]
1 = B(-1-1)(1+1)
B = [tex]-\frac{1}{4}[/tex]
1 = C(i-1)(i+1)
C = [tex]-\frac{1}{2}[/tex]
Substituting A, B, C in equation (2)
[tex]\int\frac{x^{4}}{x^{4} -1}dx[/tex] = [tex]\int\frac{1}{4(x-1)} - \frac{1}{4(x+1)} -\frac{1}{2(x^{2}+1) }[/tex]
On integration
Here [tex]\int \frac{1}{x}dx = lnx and \int\frac{1}{x^{2}+1 } dx = arctanx[/tex]
[tex]\int\frac{x^{4}}{x^{4} -1}dx[/tex] = [tex]\frac{1}{4} ln(x-1)[/tex] - [tex]\frac{1}{4} ln(x+1)[/tex] - [tex]\frac{1}{2} arctanx[/tex] + c2---------------------------------------(4)
Substitute equation (4) back in equation (1) we get
[tex]x + c1 + \frac{1}{4} ln(x-1) - \frac{1}{4} ln(x+1) - \frac{1}{2} arctanx + c2[/tex]
Here c1 + c2 can be added to another and written as c
Therefore,
[tex]\int\frac{x^{4}}{x^{4} -1}dx = x + \frac{1}{4} ln(x-1) - \frac{1}{4} ln(x+1)-\frac{1}{2} arctanx + c[/tex]
So I have zero over five and we are doing something or some form in class and I have no idea what the answer will be
Answer:
0
Step-by-step explanation:
0/5 is 0
Anything divided by zero is zero.
Answer:
Your answer:0/5 =0
Step-by-step explanation:Learned it in school... can you please mark me brainliest?!?
.Calculate the average rate of change of f(x) = 3x + 4 on the interval [2, 6]. Select any oth
Answer:
Average rate of change= 3
Step-by-step explanation:
Recall the definition of average rate of change of a function [tex]f(x)[/tex] in an interval [tex][a,b][/tex]:
Average rate of change = [tex]\frac{f(b)-f(a)}{b-a}[/tex]
In your case:
[tex]f(x) = 3x+4[/tex], and the interval [tex][a,b][/tex] i [tex][2,6][/tex], therefore:
Average rate of change = [tex]\frac{f(6)-f(2)}{6-2}=\frac{f(6)-f(2)}{4}[/tex]
Now we evaluate the function at the two requested points:
[tex]f(x)=3x+4\\f(6)=3(6)+4=18+4=22\\f(2)=3(2)+4=6+4=10[/tex], then [tex]f(6)-f(2)=22-10=12[/tex]
So finally the Average rate of change is: [tex]\frac{f(6)-f(2)}{6-2}=\frac{12}{4} =3[/tex]
Gene stated that finding
25% of a number is the same as dividing the
number by.Is Gene correct? Explain
Answer:
dividing the number by what?
_ 4. How many roots does the following equation have: 2x^4 – x^3 – 12x^2 – 25x + 5 = 0
A. 5
B. 4
C. 3
D. 2.
Answer:
B. 4
Step-by-step explanation:
The degree of the polynomial (the exponent of the highest term) is the total number of roots (including imaginary roots).
The degree of this polynomial is 4, so there are 4 roots.
Please answer. I’m very anxious about my work. The question is which equation represents the line that passes through the point (1,5) and has a slope of -2
Answer:
probably answer c
Step-by-step explanation:
help me plz I will make you brainlest
Answer:
6/10
Step-by-step explanation:
Answer:
the ratio as a fraction is 6
10
1. Find the side length of a square whose area is 252 cm². Show all your work and write the final answer in its
simplest form.
[tex]s = {a}^{2} [/tex]
[tex]252 = {a}^{2} [/tex]
[tex]a = \sqrt{252} [/tex]
[tex]a = 15.87[/tex]
That's how I did it, I don't know if it's right or not.
SOMEONE PLEASE HELP I DON'T GET THIS!!
HI umm.. I can see the thing that you need help with sorry not trying to be rude but what do you need help with?
Disney held a breakfast for parents and their children to eat with Mickey mouse. adult tickets cost $17.95 and children's tickets cost $12.95. Disney made $7355 in ticket sales from a total of 500 people that attended. How Many adults and children were at the breakfast?
Answer:
The number of children attending = 324
The number of adults attending = 176.
Step-by-step explanation:
Here, the total number of people attending = 500
Let us assume the umber of children attending the breakfast = m
So, the number of adults attending the breakfast = 500 - m
Cost of ticket for each children = $12.95
So, the cost of m children's tickets = m x ( Cost of 1 children ticket)
= m x ( $12.95) = 12.95 m .... (1)
Cost of ticket for each adult = $17.95
So, the cost of (500 -m) adults's tickets
= (500 - m) x ( Cost of 1 adult ticket) = (500 -m) x ( $17.95)
= 8,975 - 17.95 m .... (2)
Now, the total earnings from the total ticket sold = $7355
So, The earning from ( Adult's + children's tickets) = $7355
⇒ 12.95 m + 8,975 - 17.95 m = $7355
or, - 5 m = 7355 - 8975 = -1620
or, m = 1620/5 = 324
⇒ m =324
Hence the number of children attending = m = 324
The number of adults attending = 500 - m = 500 - 324 = 176.
Final answer:
There were 176 adults and 324 children present.
Explanation:
We are given the prices of adult and child tickets, as well as the total revenue and number of people. By setting up two equations, we can solve for the number of adults and children. Let's define adults as A and children as C.
From the given information, we can set up the following equations:
The total revenue from the tickets is $7355: 17.95A + 12.95C = 7355
We can use the substitution or elimination method to solve these equations. If we express C from the first equation as C = 500 - A and substitute it into the second equation, we get:
17.95A + 12.95(500 - A) = 7355
Which simplifies to:
17.95A + 6475 - 12.95A = 7355
Combining like terms, we get:
5A = 880
Thus:
A = 176
Substituting A back into the equation for C, we have:
C = 500 - 176 = 324
Therefore, there were 176 adults and 324 children at the Disney breakfast event.
Evaluate y+8 for y=-10
Answer:
Then,
y=10-8
y=2
Step-by-step explanation:
solve the equation
Answer:
Step-by-step explanation:
-10+8= -2
Solve for
-30 = 1/4 - 37
r =
Answer:
r=121/148 or r=0.81756
Step-by-step explanation:
-30=1/4-37r
37r=1/4-(-30)
37r=1/4+30
37r=1/4+120/4
37r=121/4
r=(121/4)/37
r=(121/4)(1/37)
r=121/148
What is the solution to the system of equations? 3x-6y=-12 " " x-2y=10 Use the substitution method to justify that the given system of equations has no solution. What do you know about the two lines in this system of equations?
The two lines in this system of equations are parallel
Step-by-step explanation:
Let us revise the relation between 2 lines
If the system of linear equations has one solution, then the two line are intersected If the system of linear equations has no solution, then the two line are parallelIf the system of linear equations has many solutions, then the two line are coincide (over each other)∵ The system of equation is
3x - 6y = -12 ⇒ (1)
x - 2y = 10 ⇒ (2)
To solve the system using the substitution method, find x in terms of y in equation (2)
∵ x - 2y = 10
- Add 2y to both sides
∴ x = 2y + 10 ⇒ (3)
Substitute x in equation (1) by equation (3)
∵ 3(2y + 10) - 6y = -12
- Simplify the left hand side
∴ 6y + 30 - 6y = -12
- Add like terms in the left hand side
∴ 30 = -12
∴ The left hand side ≠ the right hand side
∴ There is no solution for the system of equations
∴ The system of equations represents two parallel lines
The two lines in this system of equations are parallel
Learn more:
You can learn more about the equations of parallel lines in brainly.com/question/8628615
#LearnwithBrainly
Using substitution method, we can see the system of equation has no solution and graphically, the lines are parallel to each other and don't intersect.
What is the solution to the system of linear equations?To solve the system of equations using the substitution method, we can solve one equation for one variable and substitute it into the other equation.
Let's start by solving the second equation for x:
x - 2y = 10
x = 2y + 10
Now we substitute this expression for x in the first equation:
3x - 6y = -12
3(2y + 10) - 6y = -12
6y + 30 - 6y = -12
30 = -12
Since the equation 30 = -12 is not true, we have reached a contradiction. This means that the system of equations has no solution.
Regarding the two lines in this system of equations, we can observe that they are parallel and they don't intersect with one another.
Learn more on system of linear equation here;
https://brainly.com/question/13729904
#SPJ6
In the spinner below, the large wedges are twice the size of the smaller ones. What is true about the probability of landing on 2 and the probability of landing on 3?
A.The probability of landing on 2 is half the probability of landing on 3.
B.The probabilities cannot be predicted.
C.The probabilities are equal.
D.The probability of landing on 2 is twice the probability of landing on 3.
Answer:
C
Step-by-step explanation:
I would like to say c because it could land on anyone at any given time. I wish I knew a definite answer.
Answer:
The probability of landing on two is twice the probability of landing on 3.
Step-by-step explanation:
The reason for this is because the section 2 is twice the size of section 3 it means that the probability of landing on two is twice the probability of landing on number 3.
Solve each equation. Round to the nearest tenth, if necessary. z2 = 361
Answer:
180.5
Step-by-step explanation:
2z=361
z=361/2=180.5
8/v + 9/x=y Solve for v
The answer is v= -8x/-xy+9
Here is the step by step process (This is going to be long):
1. 9v+8x=vxy
Multiply both sides by vx
2. 9v+8x+−vxy=vxy+−vxy
−vxy+9v+8x=0
Add -vxy to both sides
3. −vxy+9v+8x+−8x=0+−8x
−vxy+9v=−8x
Add -8x to both sides
4. v(−xy+9)=−8x
Factor out the variable v
5. v(-xy+9)/-xy+9 = -8x/-xy+9
v = -8x/-xy+9
Divide both sides by -xy+9
Can I get some help please?! 100 points and Brainliest and 5 stars!THANKS!yy
Answer:
y = 12x
Step-by-step explanation:
The graph shown on the coordinate plane passes through the points (0,0) and (2,24).
The equation of the line passing through the origin is
[tex]y=mx[/tex]
To find m substitute coordinates of point (2,24):
[tex]24=2m\\ \\m=12[/tex]
So, the equation of proportioanl relationship is
[tex]y=12x[/tex]
1. The graph shows straight line passing through the origin, so this graph represents the proportional relationship.
2. The equation [tex]y=12x[/tex] determines proportional relationship, because 12 is the coefficient of direct proportionality and you can determine y for every given x multiplying by this coefficient of proportionality.
Answer:
y = 12
Step-by-step explanation:
slope = rise/run
slope = 24/2
slope = 12
y-intercept = starts at (0,0)
equation = y = mx + b
equation = y = 12x + 0
If the engine in a 1200 kg car could produce 10,000 N to accelerate from 0 to 27
m/s, how much time would that take?
Answer:
The time taken by engine of the car to accelerate is 3.24 seconds
Step-by-step explanation:
Given as :
The mass of the car = 1200 kg
The Force applied by engine to accelerate = 10, 000 N
The change in velocity = [tex]v_2[/tex] - [tex]v_1[/tex] = 27 m/s
Let The time taken by engine = t sec
And Let The acceleration = a m/s²
Now,
∵ Force is define as the product of mass and acceleration
I.e F = mass × acceleration
or, F = 1200 × a
or, 10,000 = 1200 × a
∴ a = [tex]\frac{10,000}{1200}[/tex] m/s²
I.e a = 8.33 m/s²
Now , Again
∵ Acceleration is define as the rate of change of velocity
I.e a = [tex]\dfrac{v_2-v_1}{t}[/tex]
or, a = [tex]\dfrac{27-0}{t}[/tex]
Or, t = [tex]\dfrac{27}{a}[/tex]
I.e t = [tex]\dfrac{27}{8.33}[/tex]
∴ t = 3.24 sec
So, The time taken = 3.24 seconds
Hence The time taken by engine of the car to accelerate is 3.24 seconds . Answer
hey can anyone help me with this problem
Answer:
The speed of River's mom drove for 10 miles distance is 0.234 mph.
The speed of River's mom drove for 25 miles is 10.234 mph.
Step-by-step explanation:
Given as :
The first distance cover by River's mom = 10 miles
The rate of speed = x mph
The second distance cover by river's mom = 25 miles
The rate of speed = x + 10 mph
The total driving time = 45 min
Now, According to question
[tex]Time = \frac{Distance}{Speed}[/tex]
So, [tex]45 = \frac{10}{x}+\frac{25}{x+10}[/tex]
Now dividing by 5 on both side we get;
[tex]9=\frac{2}{x}+\frac{5}{x+10}\\\\9= \frac{2(x+10)+5x}{x(x+10)}\\\\9= \frac{2x+20+5x}{x^2+10x}\\\\9(x^2+10x)= 7x+20\\9x^2+90x-7x-20=0\\9x^2+83x-20=0[/tex]
Solving this quadratic equation we get;
[tex]x=\frac{-b\±\sqrt{4ac}}{2a}[/tex]
[tex]x=\frac{-83\±\sqrt{4\times9 \times 20}}{2\times 9}\\\\x= \frac{-83\±\sqrt{720}}{18}\\ \\x= \frac{-83+87.22}{18} \ \ \ or \ \ x = \frac{-83-87.22}{18}\\\\x= 0.234 \ \ \ or\ \ \ \ x= - 9.4567[/tex]
Since speed cannot be in negative hence we will consider x= 0.234
So, The speed for 10 miles distance = x = 0.234 mph
and The speed of 25 miles = x + 10 = 0.234 + 10 = 10.234 mph
Hence The speed of River's mom drove for 10 miles distance is 0.234 mph
and The speed of River's mom drove for 25 miles is 10.234 mph
If f(x) = 3x-1 and g(x)= 4x-2 , what is h(x) when h(x) is =2 f(x) + g(x)?
Answer:
h(x) = 10x
Step-by-step explanation:
given:
f(x) = 3x-1 and g(x)= 4x-2
h(x) = 2 f(x) + g(x)
= 2 (3x+1) + (4x-2)
= 6x + 2 + 4x - 2
= 10x
The question revolves around combining functions in mathematics. To solve for h(x) when h(x) is equal to 2f(x) + g(x), we substitute f(x) and g(x) values into the equation for h(x) and simplify the resulting expression. Our calculated function h(x) = 10x - 4.
Explanation:This is a question about combining function operations. We have been given two functions f(x) = 3x-1 and g(x) = 4x-2, and asked to find h(x) = 2f(x) + g(x).
To solve it, we must substitute f(x) and g(x) into our equation for h(x):
Substitute f(x) and g(x) into h(x): h(x) = 2*(3x-1) + (4x-2).Simplify the right hand side: h(x) = 6x - 2 + 4x - 2 = 10x - 4.So, the function h(x) when h(x) is = 2f(x) + g(x) is h(x) = 10x - 4.
Learn more about Combining Functions here:https://brainly.com/question/33551477
#SPJ3
Find the sum of the first 5 terms of the series.
7 - 14 + 28 - 56+...
Answer:
The sum of the first 5 terms of the series is 77.
Step-by-step explanation:
1. Let's review the information provided to us for solving the sum of the first 5 terms of the series:
1st term = 7
2nd term = - 14
3rd term = 28
4th term = - 56
2. Let's solve the sum of the first 5 terms of the series:
Aₙ = Aₙ₋₁ * -2 ; A₁ = 7
A₁ = 7
A₂ = A₁ * -2 = 7 * - 2 = - 14
A₃ = A₂ * - 2 = -14 * - 2 = 28
A₄ = A₃ * - 2 = 28 * - 2 = - 56
A₅ = A₄ * - 2 = -56 * - 2 = 112
Sum of the first 5 terms of the series = 7 - 14 + 28 - 56 + 112
Sum of the first 5 terms of the series = 77
Here is the question
|
|
|
|
v
Answer:
16.5 square feet
Step-by-step explanation:
The logo consists of
rectangle with sides of 3 ft and 1.5 ft;trapezoid with bases 3 ft, 4 ft and height of 3 ft;triangle with base of 1.5 ft and height of 2 ft.The area of rectangle:
[tex]A_{rectangle}=1.5\ ft\times 3\ ft=4.5\ ft^2[/tex]
The area of trapezoid:
[tex]A_{trapezoid}=\dfrac{3\ ft+4\ ft}{2}\times 3 \ ft=3.5\ ft\times 3 \ ft=10.5 \ ft^2[/tex]
The area of triangle:
[tex]A_{triangle}=\dfrac{1}{2}\times 1.5\ ft\times 2 \ ft=1.5\ ft^2[/tex]
Hence, the area of logo:
[tex]A=A_{rectangle}+A_{trapezoid}+A_{triangle}=4.5\ ft^2+10.5\ ft^2+1.5\ ft^2=16.5\ ft^2[/tex]
The number m divided by 10 leaves a remainder of 1, and the number n divided by 10 leaves a remainder of 4. What will be the remainder of m+n divided by 5?
Answer: 10
Step-by-step explanation:
m divided by 10 = 1 so m is 10
n divided by 10 = 4 so n is 40
m + n is equal to 40 + 10 which is 50.
Divide 50 by 5 and you get 10!
A divided by 6 is greater than 1
Answewell 6 divided by 2 is great than 1 its 3 if this helps?
Step-by-step explanation:
The question presents an inequality, A/6 > 1. Solving this inequality yields A > 6, meaning any number greater than 6 will satisfy this equation.
Explanation:The equation given in the question is A divided by 6 is greater than 1. This can be written in mathematical terms as A/6 > 1.
To find which numbers could represent A, you have to solve this inequality. As a first step, you can multiply both sides of the inequality by 6 to isolate A. This gives us A > 6 * 1, which simplifies to A > 6.
Therefore, any number greater than 6 should satisfy the inequality A/6 > 1.
Learn more about Solving Inequalities here:https://brainly.com/question/34745580
#SPJ2
Brisa went shoe shopping this
weekend found some boots for $25
with 8% tax
Tax:
Total:
This is part of my study guide for a test I missed, please help me asap!!
Tax: $2
Total: $27
Step-by-step explanation:
Given,
Price of boots = $25
Tax = 8%
Amount of tax = 8% of price of boots
[tex]Amount\ of\ tax = \frac{8}{100}*25\\Amount\ of tax=\frac{200}{100}\\Amount\ of\ tax=\$2[/tex]
Total = Price of boots + Tax amount
[tex]Total = 25+2=\$27[/tex]
Tax: $2
Total: $27
Keywords: sales tax, addition
Learn more about addition at:
brainly.com/question/8805387brainly.com/question/8806598#LearnwithBrainly
An animal shelter has 9/10 of crates filled with animals.1/2 of the crates are holding dogs . What fraction of total number of crates are holding digs
Answer: 9/20
Step-by-step explanation:
9/10 is given as the fraction of the crates filled with animals , 1/2 of this fraction holds dog , that is
1/2 of 9/10
= 1/2 x 9/10
= 9/20
Therefore the fraction of the total number of crates holding dog is 9/20
Solve each system of equations by constructing a table. Equation 1: y = 2x + 2
Equation 2: y = -x + 8
Answer:
x=2, y=6. (2, 6).
Step-by-step explanation:
y=2x+2
y=-x+8
-------------
2x+2=-x+8
2x-(-x)+2=8
2x+x=8-2
3x=6
x=6/3
x=2
y=2(2)+2=4+2=6
You have a gift card for a coffee shop worth $90. Each day you use the card to get a coffee for $4.10. what is the value of the card after you buy your 8th coffee
Answer:
$57.20
Step-by-step explanation:
So the card starts off with $90, we spend $4.10 each day
To figure this out quick, take $4.10 and multiply it by 8
$4.10 x 8 =$32.80
Now subtract:
$90 - $32.80 = $57.20